Implementasi Iot Sebagai Sistem Akses Pintu Dengan Deteksi Wajah Dan Notifikasi Telegram - Alvian Darmawan; Fajar Septian (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Internet of Things (IoT) is a concept that describes the interaction between physical devices that are connected to the internet and can communicate with each other. ESP32-CAM which is a module that is integrated with the camera and is also equipped with a processor and sufficient memory to run face recognition applications. Implementation of a face recognition-based door access system using the ESP32-CAM module and notifications on this Telegram application can increase security and convenience for homeowners. In addition, this system has another alternative using a keypad that has physical buttons. By using the Prototyping method, this system is able to display security notifications via the Telegram application. Based on the results of the research that has been tested, the ESP32-CAM module can be connected to the internet using a wifi network, then the solenoid door lock will open when the pin password is entered correctly or a registered face ID is detected in the system.